O ensino da hist?ria recente no Uruguai (2004-2008)- as quest?es da laicidade e da disciplina Hist?ria - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
At 2004, the Frente Amplio (left parties and movements coalition) won the parliamentary and presidential elections. One of the first changes was a revision of the military period, in the juridical aspects, including human rights, and also in the educational aspect, that is, the scholar teaching about dicatatorship has entered in the agenda, and with it the advantages and problems of the teaching of recent history. From the motivations and difficulties that emerged to the incorporation of the teaching of recent history at Uruguay, the notion of ?laicidade? (laity) ? of large usage on the public debate ? as one of the strongest conditionants who grow difficult the history didactics renewing. The main objective is to understand the characteristics and working of the usage of the ?laicidade? notion, on what it refers to the history teaching. To this field of the education, there are different visions and usages of the ?history as scholar subject? and its teaching and learning processes, that are considered adequated or not according to the individual position about the theme of the ?laicidade?. With resource to documental analysis and to the production and interpretation of written interviews, it was analysed two groups of individuals involved in this debate. At a side, the politicians of the tradicional political parties (Blancos and Colorados), from their parliamentary and journalistic speeches; at the other side, the history teachers, from among were interviewed 15 teachers during the actual year. The main theorical references were the texts on historical consciousness and history didactics of J?rn R?sen (2001, 2007, 2007b) and the analysis about the relationships with the knowledge done by Bernard Charlot (1986, 2001, 2005,2006). The renewing of the history teaching in general, that represents the arrival of recent history at the classrooms stays conditioned by the indefinable notion of ?violate laicy? (violar a laicidade) in a big proportion. It was constated that the original meaning of the notion - linked to avoiding the teaching of religious dogmas in the classes ? is completely changed by a ?political shape? that unites this notion with the idea of a objective and neutral education. Because of this, the ?usage? of the laicy concept revealed to be a key to enter the analysis in the different ?usagens of teached history? and over the vision that is got ?about? and ?from? the different individuals that make the teaching and learning process (except the students that were no part of this research). By a side, the politicians consider ?laic? and, because of this, accepted, a history without conflicts ? lineal, nationalist and liberal (and, of course, objective and neutral) that honour the supposed tabula rasa that the student would represent. The teachers divide in whose fear problems caused in the confrontation of those ?social accepted? rules (and ends ?institucionalizing? themselves accepting those rules) and the ones who see a trap in the desired objectivity or neutrality. The prominence of this research is at identifying the ?laicidade? as a notion at the same time indefiniable and insindiously condicionater of the practices, individuals and knowledges to the history teaching in Uruguay. The research allows proposing a revision of the ?laicidade? notion, in the meaning of maintaining this role of definition of a public space, but pledging criteria that can also be public, that means, intersubjectively constructed.
Keywords: did?tica da hist?ria; usos da hist?ria; laicidade; hist?ria recente; identidades sociais; history didactics; history usages; laicy; recent history; social identities; CNPQ::CIENCIAS HUMANAS::EDUCACAO